Tannin-rich strawberry vines fermented with lactic acid bacteria improve growth performance in Hu sheep - Lu, Wenguang; Zhang, Zimo; Zhu, Zhigang; Li, Yusen; Fang, Zhenyu; Wang, Siqi; Zhou, Shuying; Zhang, Ling; Zhang, Yunhua; Chen, Lijuan (Frontiers in Veterinary Science, 2025)
BackgroundStrawberry vines are nutrient-rich but contain high levels of tannins and have a moisture content of up to 70%, making ensiling a crucial strategy for preserving their nutritional value.MethodsTwo lactic acid bacteria (LAB) strains, designated Z and R, were isolated from strawberry vines. Fresh strawberry vines were ensiled in three groups: two experimental groups inoculated with strains Z and R (1.0 × 106 CFU/g fresh weight) and a control group (CK) treated with physiological saline. Samples were collected on days 1, 3, 5, 7, 15, 30, and 45 of fermentation for analysis. The LAB-treated silage was subsequently incorporated into Hu sheep diets to evaluate its effects on growth performance.ResultsThe identification results indicated that strain Z was Lactiplantibacillus plantarum and strain R was Lactococcus lactis. Both treatment groups exhibited significantly higher crude protein (CP) content (p < 0.05) and markedly lower NH3-N content (p < 0.05) compared to the CK group. Notably, supplementation with L. plantarum significantly reduced tannin content in strawberry vines (p < 0.05) compared to other two groups. By day 3, the pH values in the treatment groups were significantly lower than those in the CK group (p < 0.05), with L. plantarum treatment group showing significantly lower pH than L. lactis group throughout days 3 to 15 (p < 0.05), indicating more rapid silage stabilization. In terms of fermentation quality, lactic acid (LA) and acetic acid (AA) contents in the treatment groups were significantly higher than in the CK group (p < 0.05). Microbial community analysis demonstrated that both treatment groups effectively suppressed the growth of harmful microorganisms at both the phylum and genus levels, with Lactiplantibacillus genus abundance reaching 54.18% in L. plantarum group compared to only 0.98% in CK by day 3. Furthermore, when used as roughage for Hu sheep, LAB-fermented strawberry vine silage significantly improved average daily gain (ADG) (p < 0.05) and enhanced the apparent digestibility of dry matter (DM), neutral detergent fiber (NDF), and CP (p < 0.05). Inclusion of strawberry vine silage fermented by L. plantarum markedly reduced the relative abundances of the predominant ruminal genera Clostridium and Ercella.ConclusionLAB supplementation significantly improved the silage quality of strawberry vines by effectively inhibiting putrefactive processes during the late fermentation stage of high-moisture silage. Moreover, the use of strawberry vine silage as feed markedly enhanced the growth performance in Hu sheep.